TRANSESTERIFIKASI MINYAK GORENG BEKAS MENGGUNAKAN KATALIS DARI LIMBAH GERGAJIAN KAYU MATOA (Pometia pinnata): VARIASI RASIO MOL METANOL TERHADAP MINYAK - Aronggear, Pitornela Ribka; Santi, Darma; Langsa, Markus Heryanto; Lisna Efiyanti, Lisna Efiyanti (FMIPA Universitas Papua, 2024)
Utilization of the sawn waste of matoa (Pometia pinnata) wood from Manokwari is carried out to provide an alternative choice of transesterification reaction catalyst sources that utilize wood processing waste materials. This study aimed to determine the character of the synthetic ash material by calcination method at 500 °C. In addition to testing the catalytic activity of synthetic wood ash in the transesterification reaction of used cooking oil, the mole ratio of methanol to used cooking oil was 3:1 and 9:1. The characterization results indicated the alkali metal components, in the form of Na and K, were respectively 20.7750 and 4.8625 mg/L. The content of alkaline earth metals in the form of Ca is 27.3125 mg/L. The percentage yield of transesterification or total methyl ester conversion at a ratio of 3:1 was 47.24%. Product distribution at a ratio of 3:1, namely methyl palmitate (26.34%) and methyl oleate (20.90%). The yield percentage of transesterification or total methyl ester conversion at a ratio of 9:1 was 64.74%. Product distribution at a ratio of 9:1, namely methyl palmitate (31.70%) and methyl oleate (33.04%).